Wciąż narodowe czy już postnarodowe? Przemiany koncepcji obywatelstwa wobec doświadczenia transnarodowości - Hildebrandt-Wypych, Dobrochna (Wydawnictwo Naukowe UAM, 2013)
The aim of the text is to present the category of post-national citizenship developed in relation to, or even in opposition to the earlier version of the traditional national citizenship in a liberal society. Attention is drawn to the importance of the experience of transnationalism for the development of new civic identities, transcending beyond the nation-states boundaries. The focus will be on key elements of the scientific debate on the interdependence between the national and the post-national perspective in contemporary attempts to conceptualize the category of citizenship. The increased role of post-national forms of civic participation is explained by reference to broader processes, including further individualization and emphasis on selfrealization in personal life, the creation of transnational communities, internationalization of human rights protection, as well as the transformation of the very nation-state and its range of obligations to the citizens. Moreover, the text refers to the counter-arguments against the thesis of a slow, yet inevitable weakening of the link between citizenship and nationality, including examples of legislative and administrative actions of Western states aimed at strengthening the national citizenship concept.
National or post-national? Transformation of the concept of citizenship and the experience of transnationalism
Keywords: national citizenship; post-national citizenship; nation-state; transnationalism; civic identity